Effect of oral potassium supplementation on urinary potassium excretion and its diagnostic value for primary aldosteronism - Ke Zhang; Xiyun Deng; Zhuoran Li; Chen Yi; Jianqiong Kong; Yunhong Wang (Clinical and Experimental Hypertension)
Objectives We aimed to: (1) explore the effect of oral potassium supplementation on urinary potassium excretion, and (2) evaluate the value of urinary potassium-related indicators in distinguishing primary aldosteronism (PA) from non-PA patients.Design and methods A prospective study of 20 patients with hypertension and hypokalemia caused by renal potassium loss between November 2023 and April 2024 was conducted. Demographic features, 24-hour urine collection before and after potassium supplementation were all collected.Results The patients had a mean age of 49.38 years and 70% were male. Following a median potassium supplement dose of 8.50 g, serum potassium increased from 3.25 to 3.90 mmol/L (p < .001), and 24-hour urinary potassium (24 h UK) rose from 41.40 to 59.75 mmol/24 h (p = .004). After supplementation, 20% of patients had decreased 24 h UK, while 25%, 25%, and 40% showed increases of 0–10, 10–20, and > 20 mmol/24 h. Urinary-to-serum potassium ratio (USR) decreased in 40% of patients, while it increased by 0–5, 5–10, and > 10 L/24 h in 25%, 25%, and 10% of patients, respectively. Both 24 h UK and USR after repletion predicted PA with moderate-to-high accuracy (AUC = 0.808 for both). The optimal cutoff of 24 h UK and USR after supplementation were 51 mmol/24 h and 17.43 L/24 h. The AUC for 24 h USR and 24 h UK before repletion in predicting PA were 0.788 and 0.652, respectively.Conclusions Urinary potassium does not increase proportionally with serum potassium levels or the oral potassium dose, showing individual variability. Post-supplementation urinary potassium has greater diagnostic value for distinguishing PA than pre-supplementation indicators.